2020
DOI: 10.1111/tpj.14783
|View full text |Cite
|
Sign up to set email alerts
|

Plant tissue succulence engineering improves water‐use efficiency, water‐deficit stress attenuation and salinity tolerance in Arabidopsis

Abstract: SUMMARY Tissue succulence (ratio of tissue water/leaf area or dry mass) or the ability to store water within living tissues is among the most successful adaptations to drought in the plant kingdom. This taxonomically widespread adaptation helps plants avoid the damaging effects of drought, and is often associated with the occupancy of epiphytic, epilithic, semi‐arid and arid environments. Tissue succulence was engineered in Arabidopsis thaliana by overexpression of a codon‐optimized helix‐loop‐helix transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 119 publications
0
31
1
Order By: Relevance
“…Besides increased cell size, the authors also reported a significant decrease in cell wall thickness-another feature typically observed in CAM plants (Yang et al, 2015). A follow-up study in Arabidopsis reported significant increases in cell size, succulence, decreased intercellular air space and WUE (Lim et al, 2020). Thus, (tissuespecifically) overexpressing VvCEB1op in the context of engineering CAM could indeed be a promising strategy to engineer more drought-resistant crops.…”
Section: Overcoming Vacuolar Storage Constraints By Increasing Cell Sizementioning
confidence: 85%
“…Besides increased cell size, the authors also reported a significant decrease in cell wall thickness-another feature typically observed in CAM plants (Yang et al, 2015). A follow-up study in Arabidopsis reported significant increases in cell size, succulence, decreased intercellular air space and WUE (Lim et al, 2020). Thus, (tissuespecifically) overexpressing VvCEB1op in the context of engineering CAM could indeed be a promising strategy to engineer more drought-resistant crops.…”
Section: Overcoming Vacuolar Storage Constraints By Increasing Cell Sizementioning
confidence: 85%
“…in genotypes and ecotypes or in extremophytes. The development of xerophytic traits and succulence are typical adaptive mechanisms for withstanding dehydration (Kuromori et al, 2018;Geilfus, 2019;Laxa et al, 2019;Xu et al, 2019;Lim et al, 2020). Interactions between plant structure, function and the environment need to be investigated during various phases of plant development at the organismal, cellular and molecular levels in order to obtain a full picture of adaptation (Barnábas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, proline, as an osmotic regulator, enzyme denaturation protector and macromolecule assembly stabiliser, allows additional water from the environment to be reserved in cells, thereby allowing water potentials to decrease; this can then be observed in an increase in cell area, a large cell area and roundness in plant’s tissue can be associated to the succulence of the plant. As reported in other studies succulence is the ability of some plants to store water and to be somehow independent of external water supply, this can be also linked to the anatomical adaptation during salinity tolerance 16 , 17 . Moreover, stomatal conductance is reduced when plants are exposed to high salinity, which leads to the generation of reactive oxygen species (ROS), while CO 2 fixation is reduced, which is reflected in changes in contents of plant pigments such as chlorophylls and carotenoids 18 .…”
Section: Introductionmentioning
confidence: 56%